Green Finance And Perceived Financial Performance From Employees Perspectives In Nepalese Commercial Banks - Chapagain, Jamuna Devi; Rana, Bikash (Devkota Journal of Interdisciplinary Studies, 2025)
The effect of green banking practices on Nepalese commercial banks’ financial performance is investigated in this study. With increasing global emphasis on sustainable finance, the research investigates how specific green banking components regulatory policies, stakeholder demand, green investment, employee environmental training, and green product services affect banks’ profitability and operational efficiency from the perspective of banking employees.385 employees of Nepal’s commercial banks were given a structured questionnaire as part of a quantitative study design. To evaluate the connections between perceived financial performance metrics and green banking practices, statistical methods such as multiple regression analysis and correlation were used. The findings show that stakeholder demand, employee environmental training, regulatory policies, and green product services all significantly improve financial performance. However, green investment does not demonstrate a significant effect, indicating potential challenges in its early-stage implementation within Nepalese banks. These findings align with global evidence supporting the role of ESG practices in enhancing financial outcomes, particularly in emerging markets. This study adds empirical observations from internal stakeholders and bank employees to the little body of literature on green finance in emerging nations. This highlights the practical implications of green banking in enhancing financial performance while promoting sustainability. The findings are valuable for bank executives, policymakers, and regulatory bodies aiming to foster environmentally responsible banking practices without compromising financial viability.